2003
DOI: 10.2337/diabetes.52.8.2102
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cβ Selective Inhibitor LY333531 Attenuates Diabetic Hyperalgesia Through Ameliorating cGMP Level of Dorsal Root Ganglion Neurons

Abstract: Streptozocin (STZ)-induced diabetic rats show hyperalgesia that is partially attributed to altered protein kinase C (PKC) activity. Both attenuated neuronal nitric oxide synthase (nNOS)-cGMP system and tetrodotoxin-resistant (TTX-R) Na channels in dorsal root ganglion neurons may be involved in diabetic hyperalgesia. We examined whether PKC␤ inhibition ameliorates diabetic hyperalgesia and, if so, whether the effect is obtained through action on neurons by testing nociceptive threshold in normal and STZ-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 53 publications
2
30
2
Order By: Relevance
“…In this study, the immunohistochemical results clearly demonstrated the in situ translocation of PKC-␣ isoform from the membrane to the cytoplasm, which accords with the results of our Western blot analysis. Contrariwise, PKC-␤II isoform in diabetic transgenic mice was slightly elevated, consistent with the data obtained from the STZ rat model (35,36). Interestingly, ARI treatment corrected the alterations of both PKC-␣ and -␤II isoforms.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, the immunohistochemical results clearly demonstrated the in situ translocation of PKC-␣ isoform from the membrane to the cytoplasm, which accords with the results of our Western blot analysis. Contrariwise, PKC-␤II isoform in diabetic transgenic mice was slightly elevated, consistent with the data obtained from the STZ rat model (35,36). Interestingly, ARI treatment corrected the alterations of both PKC-␣ and -␤II isoforms.…”
Section: Discussionsupporting
confidence: 78%
“…Our study revealed that the pain sensation in diabetic animals was initially hyperalgesic followed by late hypoesthesia in the presence of a progressive delay of both MNCV and SNCV. This result argues against the results obtained from the STZ-induced diabetic rat (36) and the diabetic mice with short duration (40). We only conducted the paw withdrawal test under mechanical pressure for the pain sensation and therefore need further evaluation using different methods such as a test for thermal sensitivities.…”
Section: Discussioncontrasting
confidence: 46%
“…In rats with streptozotocin-induced diabetes, decreases in the number of NOS-expressing neurons, in nNOS expression and cGMP content were revealed in DRGs together with mechanical hyperalgesia that all were completely prevented by insulin treatment (360,628). In subsequent studies, however, no significant change in nNOS mRNA levels was observed in DRG neurons; moreover, increased NOS activity was revealed as late as 12 mo after diabetes induction (446,806).…”
Section: Experimental Paradigms Yielding Inconsistent Results Regardimentioning
confidence: 94%
“…Traditional approaches to PKC inhibition have been marred by toxicity and lack of specificity. However, more recently, a range of less toxic and more specific approaches to PKC inhibition (21), including specific ␤-isoform inhibitors such as ruboxistaurin (LY 333531), that have been used in preclinical and clinical studies of diabetic retinopathy (22), neuropathy (23), and vascular dysfunction (24) have been developed. In diabetic nephropathy, ruboxistaurin is currently undergoing clinical eval- (17,26).…”
Section: Discussionmentioning
confidence: 99%